Kersen leaf extract gel (Muntingia calabura L.) to Improve the healing of perineal wounds in postpartum mothers - Rahmatia, Diyah Annisa; Wijayanti, Krisdiana; Ramlan, Djamaluddin (MEDISAINS, 2022)
Background: Delivery processes experience 90% perineal rupture—worldwide. Previous research on test animals proved the effect of cherry leaf gel on wound healing can kill microorganisms, increase collagen, and repair wound tissue. However, no research has been found on healing perineal wounds in postpartum mothers using cherry leaf gel, so this research is necessary.Purpose: Making and testing kersen leaf extract gel to improve perineal wound healing for postpartum women.Method: This is a quasi-experiment with a pre-post-test with a control group design. The sample consisted of 26 postpartum women with perineal injuries grade 2, divided into two groups (Intervention and control). The intervention was given a combination of kersen leaf gel 25% with antibiotic 2x1 for seven days, and the control group was only given the antibiotic. Perineal wound healing was assessed using the REEDA score. The data analysis used the Mann-Whitney test.Results: The results showed that the average REEDA score was lower in the intervention group than in the control group on day 3 (5.00±1.155 vs. 5.85±0.801; p=0.038), day 5 (2.31±0.650 vs. 3.23±1.013; p=0.029), and day 7 (0.23±0.439 vs. 1.15±0.987; p=0.039).Conclusion: Kersen leaf extract gel is effective in improving perineal wound healing in postpartum women.